2016
DOI: 10.1371/journal.pone.0148844
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Patterns in Patients with Multiple Trauma: A Systematic Review of Autopsy Studies

Abstract: PurposeA high percentage (50%-60%) of trauma patients die due to their injuries prior to arrival at the hospital. Studies on preclinical mortality including post-mortem examinations are rare. In this review, we summarized the literature focusing on clinical and preclinical mortality and studies included post-mortem examinations.MethodsA literature search was conducted using PubMed/Medline database for relevant medical literature in English or German language published within the last four decades (1980–2015). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 24 publications
(25 reference statements)
7
81
1
13
Order By: Relevance
“…In this study, the highest rate of reported death (n = 64%) related to the neurological disorders' was started from the age of 50 to 100 years old. This is in agreement with previous publications that recommended an in-depth analysis for age, gender-specific mortality rates [17] and other factors that affecting the pattern of mortality [16]. In another publication the mortality rates related to the tumors of central nervous system reported to be increased within all age groups, most significantly in patients aged 70 years or older [18].…”
Section: Disscussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the highest rate of reported death (n = 64%) related to the neurological disorders' was started from the age of 50 to 100 years old. This is in agreement with previous publications that recommended an in-depth analysis for age, gender-specific mortality rates [17] and other factors that affecting the pattern of mortality [16]. In another publication the mortality rates related to the tumors of central nervous system reported to be increased within all age groups, most significantly in patients aged 70 years or older [18].…”
Section: Disscussionsupporting
confidence: 91%
“…Chauny et al, in 2016 confirmed that special care may be required for patients with serious mechanism of injury, those display marks of neurologic worsening, and patients presenting with extreme anticoagulation or getting antiplatelet co-medication [15]. Pfeifer et al, in 2016 reported that around 50 to 60 % of trauma patients die due to their injuries prior to arrival at the hospital [16]. In this study, the highest rate of reported death (n = 64%) related to the neurological disorders' was started from the age of 50 to 100 years old.…”
Section: Disscussionmentioning
confidence: 99%
“…A systematic review published in 2016 summarizes trauma studies performed over 30 years, and identifies that brain injury, exsanguination, and a combination of brain injury and severe bleeding were the leading causes of death after trauma [93]. Bleeding has been shown to be the leading cause of preventable deaths among trauma patients [94].…”
Section: Traumamentioning
confidence: 99%
“…The trimodal distribution of death following major trauma, consisting of immediate (within 1 h of injury), early (within hours of injury) and late (within several weeks of injury) deaths, has been replaced in mature trauma systems by a unimodal distribution. The majority of deaths occur in the first several hours after injury, predominantly from haemorrhage and brain injury. These observations highlight the need to focus on immediate postinjury care.…”
mentioning
confidence: 99%